Answer:
-28 + -1 = -29
-14 + -2 = -16
-7 + -4 = -11
-4 + -7 = -11
-2 + -14 = -16
-1 + -28 = -29
1 + 28 = 29
2 + 14 = 16
4 + 7 = 11
7 + 4 = 11
14 + 2 = 16
28 + 1 = 29
Step-by-step explanation:
Answer:
1/(x^3 + 6x^2 + 12x + 8)
Step-by-step explanation:
The first thing we do is rationalize this expression. (2+x)^-3 is written as
1/(2+x)^3
Then from there we can foil out the denominator. It is easiest to foil (2+x)(2+x) first and then multiply that product by (2+x).
(2+x)(2+x) = 4 + 4x + x^2
(4+4x+x^2)(2+x) = 8+8x+2x^2+4x+4x^2+x^3.
Then we combine like terms and put them in order to get:
x^3 + 6x^2 + 12x + 8
And of course we can't forget that this was raised to the negative third power, so our answer is 1/(x^3 + 6x^2 + 12x + 8)
Answer:
2
Step-by-step explanation:
Its pretty easy math
Answer:
Step-by-step explanation:
1/3 0.333 repeated 0.333 times 100 =33.333…%